Workshop series on the role of institutions in East Asian development: Institutional foundations of innovation and competitiveness in East Asia - Werner Pascha; Cornelia Storz; Markus Taube (University of Duisburg-Essen, Institute of East Asian Studies (IN-EAST), 2007)
The discussion paper summarizes the results of a workshop that focussed on the institutional foundations of innovation and competitiveness in East Asia. The following papers are contained: 'Transitional Institutions, Institutional Complementarities and Economic Performance in China. A "Varieties of Capitalism" Approach', 'The Current State of Research on Networks in China's Business System', 'Recent Changes to Korea's Innovation Governance', 'Standardization and Institutional Complementarities in Japan - Empirical Results from SAP R/3 Implementations in Japanese Automotive Suppliers'.
Keywords: 330; East Asia; Japan; China; Korea; institutional change; competitiveness; innovation; Institutionalismus; Innovation; Internationaler Wettbewerb; Ostasien